Hard cocoa butter replacers from mango seed fat and palm stearin - Jahurul, Md. Haque Akanda; Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Ferdosh, Sahena; Abedin, Md. Zainul; Mohamed, Awang; Abd Kadir, Mohd Omar (Elsevier, 2014)
The blending effects of mango seed fat (MSF), extracted using supercritical fluid, and palm stearin (PS) to formulate hard cocoa butter replacers (CBRs), were investigated. The triglycerides (TG), thermal properties and solid fat content (SFC) of the formulated blends were determined using different chromatographic and thermal techniques. All the blends had three main TGs; namely, 1,3-dipalmitoyl-2-oleoylglycerol (POP) (8.6 to 17.7%), 1-palmitoyl-2-oleoyl-3-stearoyl-glycerol (POS) (12.6 to 19.6%), and 1,3-distearoyl-2-oleoyl-glycerol (SOS) (37.2 to 31.4%), with SOS being the major component. The melting peak temperatures gradually increased and shifted towards higher temperatures with PS. The crystallization onset temperatures increased, while the offset decreased with PS. The SFC did not drop to 0% at 37.5 °C, which was shifted to 0% at and above 40 °C for some blends. The studies revealed that CBRs could be prepared by blending MSF and PS, and they could be utilized by chocolate manufacturers in tropical countries.